2008
DOI: 10.1007/s11947-008-0084-8
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic and Spectroscopic Evaluation of Inactivation of Staphylococcus aureus by Pulsed UV Light and Infrared Heating

Abstract: Pulsed UV light and infrared heat-treated Staphylococcus aureus cells were analyzed using transmission electron microscopy to identify the cell damage due to the treatment process. A 5-s treatment with pulsed UV light resulted in complete inactivation of S. aureus even after enrichment. The temperature increase during the pulsed UV light treatment was insignificant, which suggested a nonthermal treatment. S. aureus was also infrared heat treated using an infrared heating system with six infrared lamps. Five mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(83 citation statements)
references
References 24 publications
1
76
0
2
Order By: Relevance
“…According to Fine and Gervais (2004), this overheating may cause vaporization and generate a small steam flow to cause membrane destruction. Krishnamurthy et al (2008) also suggested photophysical effects of PL on S. aureus in phosphate buffer treated for 5 s, caused by disturbances of intermittent high energy pulses, since temperature increase during treatment was negligible (2°C). S. aureus exhibited cell wall damage, cytoplasmic membrane shrinkage, cellular content leakage, and mesosome disintegration based on transmission electron microscopy and Fourier transform infrared spectroscopy observations.…”
Section: Microbial Inactivation By Plmentioning
confidence: 95%
“…According to Fine and Gervais (2004), this overheating may cause vaporization and generate a small steam flow to cause membrane destruction. Krishnamurthy et al (2008) also suggested photophysical effects of PL on S. aureus in phosphate buffer treated for 5 s, caused by disturbances of intermittent high energy pulses, since temperature increase during treatment was negligible (2°C). S. aureus exhibited cell wall damage, cytoplasmic membrane shrinkage, cellular content leakage, and mesosome disintegration based on transmission electron microscopy and Fourier transform infrared spectroscopy observations.…”
Section: Microbial Inactivation By Plmentioning
confidence: 95%
“…Attempts to elucidate the mechanism by which pulsed light kills bacteria and yeasts have been published (10,(53)(54)(55)(56)(57). In the present study, multiple assays were performed to provide insight into the mechanism of virus inactivation by pulsed light.…”
Section: CMmentioning
confidence: 99%
“…IR heating can be also used to inactivate bacteria, spores, yeast, and molds in both liquid and solid for drying low moisture foods and baking of rice cakes (Sarantinos and Black 1996;Zarkadas and Wiseman 2001;Krishnamurthy et al 2009;Turabi et al 2008;Sabanis and Tria 2009).…”
Section: Introductionmentioning
confidence: 99%